Hubungan Sosial Ekonomi dengan Status Gizi Pada Anak Balita di Wilayah Kerja Puskesmas Birem Bayeun Kabupaten Aceh Timur Provinsi Aceh Tahun 2022 - Nova Radiani Br Hsb; Dwi Indah Oktaviani (Departement of Mathematics Education, 2023)
Nutritional status is a state body that is the end result of a balance between nutrients into the body and its utilization. If the balance had been disturbed, such as protein and energy expenditure more than revenues, there will be protein-energy malnutrition, and if prolonged will arise known problems with severe PEM or malnutrition. The purpose of this study was to determine the Socio-Economic Relations with Nutritional Status in Children Toddlers in Puskesmas Birem Bayeun East Aceh district of Aceh province in 2022. This research is an analytic cross-sectional design. all mothers with children under five in Puskesmas Birem Bayeun East Aceh District, amounting to 1,946 families in 2022 with a total sample of 95 respondents taken with Stratified Random Sampling technique. Research conducted on 95 respondents who are in Puskesmas Birem Bayeun East Aceh in 2022, the majority by 55 respondents (57.9%) have incomes in the high category. Results of statistical test by Chi - Square (X2) showed no association with socioeconomic nutritional status of children under five with a value (Pvalue < α= 0.001 <0.05). This study is expected to be more understanding of materials to parents about the importance of compliance with the nutritional status of children to reduce the risk of malnutrition in children and expected results of the research can be used as input to the associated health instasi, regarding the fulfillment of the nutritional status of children under five in particular in the Work Area PHC Birem Bayeun East Aceh district.